2016
DOI: 10.1007/978-3-319-22533-3_2
|View full text |Cite
|
Sign up to set email alerts
|

Early Changes in Brain Oxygen Tension May Predict Outcome Following Severe Traumatic Brain Injury

Abstract: We report on the change in brain oxygen tension (PbtO2) over the first 24 h of monitoring in a series of 25 patients with severe traumatic brain injury (TBI) and relate this to outcome. The trend in PbtO2 for the whole group was to increase with time (mean PbtO2 17.4 [1.75] vs 24.7 [1.60] mmHg, first- vs last-hour data, respectively; p = 0.002). However, a significant increase in PbtO2 occurred in only 17 patients (68 %), all surviving to intensive care unit discharge (p = 0.006). Similarly, a consistent incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(40 citation statements)
references
References 22 publications
5
35
0
Order By: Relevance
“…1,110 Additionally, a RCT published in 2016 111 showed that strict fever control resulted in similar clinical outcomes as prolonged TH. The most recent systematic reviews 1,112 have also reported conflicting results. 110 A 2016 meta-analysis 111 was unable to demonstrate improved survival and suggested that TH may increase the risk of new pneumonia and cardiovascular complications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,110 Additionally, a RCT published in 2016 111 showed that strict fever control resulted in similar clinical outcomes as prolonged TH. The most recent systematic reviews 1,112 have also reported conflicting results. 110 A 2016 meta-analysis 111 was unable to demonstrate improved survival and suggested that TH may increase the risk of new pneumonia and cardiovascular complications.…”
Section: Introductionmentioning
confidence: 99%
“…Frequent and long duration of cerebral hypoxaemic episodes in trauma patients have been repeatedly found to be significantly associated with poor outcome 139. By manipulating CPP and ICP, and optimising PaO 2 , PaCO 2 and blood haemoglobin concentration, it is possible to improve PbtO 2 112.…”
mentioning
confidence: 99%
“…7,[10][11][12]15,16,[24][25][26][27][28][29][30] For these epidural and subdural hematomas, whether hemispheric or bihemispheric, their pre-3% HTS and post-3% HTS infusion differences in r c SO 2 and CBVI readings demonstrated the significance of the concomitant effect of increased ICP on the contralateral cerebral physiology. 7,[10][11][12]15,16,[26][27][28][29][30] In the subdural compared with the epidural hematoma patients, the subdural patients had significantly lower ipsilateral and contralateral r c SO 2 and CBVI readings than did the epidural hematoma patients, and the subdural hematoma patients' contralateral hemisphere was more responsive to the 3% HTS infusion effect. 7,[10][11][12]15,16,[26][27][28][29][30] The lower contralateral r c SO 2 and CBVI readings could be the result of the initial trauma-induced intraparenchymal bleeding or expanding hematoma with hemorrhagic site expansion and increased ICP as an indirect effect causing increased pressure on the contralateral cerebral tissue, thus decreasing contralateral cerebral perfusion, oxygen delivery, and metabolism.…”
Section: Discussionmentioning
confidence: 92%
“…As in prior cardiovascular and neurosurgical cerebral oximetry with CBVI studies, cerebral oximetry in this study has demonstrated its functionality in detecting abnormal cerebral pathophysiology location and ability to identify and trend changes correlated with 3% HTS infusions. 7,[10][11][12][15][16][17][18][19][20][25][26][27][28][29][30] Significant simultaneously improved CBVI readings substantiated that the 3% HTS infusion effect correlated with hemispheric r c SO 2 readings changes. 7,12,[15][16][17][18][19][20][25][26][27][28][29][30] These CBVI changes demonstrated that the 3% HTS-induced changes in hemispheric r c SO 2 readings were reflective of 3% HTS inducing an improved regional cerebral tissue and bihemispheric perfusion similar to the invasive 3% HTS TBI studies.…”
Section: Discussionmentioning
confidence: 97%
“…Sedation remains a nonsuperior therapeutic option in episodes of compromised PbtO 2 , which have been associated with increased mortality and worse prognosis. [52][53][54] It is likely that specific subgroups of patients benefit more than others from specific interventions. Future investigations defining which patients benefit most from sedation will enable its use to correct PbtO 2 reductions in a more targeted manner.…”
Section: Neurointensive Care Unit Sedation Practicementioning
confidence: 99%